2012
DOI: 10.1111/j.1464-410x.2011.10793.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of loin pain suspected to be renal colic with papaverine hydrochloride: a prospective double‐blind randomised study

Abstract: Study Type – Therapy (RCT) Level of Evidence 1b What's known on the subject? and What does the study add? Results of our study showed that intravenous papaverine hydrochloride plus suppository sodium diclofenac were more effective than diclofenac sodium suppository alone in the treatment of acute renal colic. Therefore, intravenous papaverine hydrochloride may be a beneficial supplemental therapy to relieve renal colic pain, particularly in combination with NSAIDs. OBJECTIVE To assess the efficacy of papaveri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 10 publications
0
15
0
Order By: Relevance
“…The only reported side effect of papaverine is dizziness, which occurs in only a small percentage of patients (2%) (42). Snir et al concluded that using papaverine in the treatment of renal colic is as effective as sodium diclofenac in the management of patients with renal colic pain in the short term, and can be effective if there are contraindications for the use of NSAIDs; however, the analgesic effect of diclofenac in controlling pain lasts longer than papaverine (43).…”
Section: Resultsmentioning
confidence: 99%
“…The only reported side effect of papaverine is dizziness, which occurs in only a small percentage of patients (2%) (42). Snir et al concluded that using papaverine in the treatment of renal colic is as effective as sodium diclofenac in the management of patients with renal colic pain in the short term, and can be effective if there are contraindications for the use of NSAIDs; however, the analgesic effect of diclofenac in controlling pain lasts longer than papaverine (43).…”
Section: Resultsmentioning
confidence: 99%
“…It is also used to prevent spasmodic pains [36]. Papaverine dosage depends on the type of disease; as a pain killer it can be administered by IV at doses ranging from 30 to 120 mg every 3 h and in this study it was used in the physiological dosage range [37,38]. Circular dichroism (CD) is an excellent tool for studying secondary structure [39].…”
Section: Discussionmentioning
confidence: 99%
“…The latter reaches in most cases below the iliac bifurcation and may be followed by symptomatic pulmonary embolism in up to 27% of cases [ 18 , 19 ]. The incidence of the concomitant bland thrombus was found to be higher in more advanced levels of tumor thrombus [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…If intrahepatic IVC or renal veins are involved, patient may present symptoms of renal congestion and Budd–Chiari syndrome (i.e., hepatomegaly, ascites, and jaundice) [ 23 – 25 ]. Patients with chronic IVC obstruction develop venous collaterals diagnosed either radiographically (e.g., dilated lumbar-hemiazygos veins), or clinically (e.g., dilated abdominal wall veins) [ 22 , 26 ]. The presence of collateral venous pathways, deep and superficial, is responsible for the lack of severe IVC obstruction symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation